Studies on Molybdenum(III)-Halomine Titration in Aqueous Hydrochloric Acid Medium - Vishnumurthy, K.A.; Nayak, P.Vasudeva; Vasant Kumar Pal, K. (Asian Journal of Chemistry, 2010)
The quantitative reduction of N-halo- and N,N-dihaloarylsuphonarnides with molybdenum(III) in aqueous hydrochloric acid medium has been studied in detail. The analytical utility of these redox systems for titrimetric analysis has also been tested.